Analysis of Routing Protocol of Wireless Sensor Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Severalroutingprotocolshavebeenproposedtomaximizethesensornetworkslifetime.However,highlyrestricted resource and frequent node failure are two major challenges. Relevant technical research into wireless sensor network has become an issue of intense interest. In recent years, achievements in research on routing protocol of wireless sensor network have been summarized, analyzed and compared. Features of wireless sensor networks have been introduced and key factors of its routing protocol design have been introduced. According to the realization features of protocol, routing protocol of wireless sensor network has been divided into five categories, and each category of important protocols has been elaborated and analyzed. Finally, the features of these protocols are summarized and compared and the development trend of such research has been forecasted.